Structural characteristics of antigen-specific suppressor factors: definition of 'constant' region and 'variable' region determinants. - Kontiainen, S; Feldmann, M (1979)
Anti-suppressor factor antisera, prepared either in rabbits (R alpha SF) or in syngeneic (CBA) mice (M alpha SF) by repeated immunisation with antigen purified CBA antigen specific suppressor factor reactive to KLH was shown to abolish the suppression caused by suppressor factors (SF) in vitro. R alpha SF inhibited the function of all SF regardless of their strain of origin or their antigen specificity suggesting that it recognized 'constant region'-like determinants in SF molecules. It did not have any effect on antigen-specific helper factors. Syngeneic M alpha SF only abolished the function of suppressor (or helper) factors which were KLH-specific, and only provided they were derived from the appropriate strains of mice; thus resembling the effects of anti-idiotype antibody. No linkage to MHC could be demonstrated but there was some evidence of possible association with allotype. A schematic structure of the SF molecule is suggessted on the basis of these findings with antisera to SF.